1989
DOI: 10.1038/342711a0
|View full text |Cite
|
Sign up to set email alerts
|

PDGF induction of tyrosine phosphorylation of GTPase activating protein

Abstract: The cascade of biochemical events triggered by growth factors and their receptors is central to understanding normal cell-growth regulation and its subversion in cancer. Ras proteins (p21ras) have been implicated in signal transduction pathways used by several growth factors, including platelet-derived growth factor (PDGF). These guanine nucleotide-binding Ras proteins specifically interact with a cellular GTPase-activating protein (GAP). Here we report that in intact quiescent fibroblasts, both AA and BB homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
167
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(179 citation statements)
references
References 27 publications
12
167
0
Order By: Relevance
“…Tyrosine phosphorylation of mammalian GAP has long been known (Ellis, Moran, McCormick, & Pawson, 1990;Molloy et al, 1989;Park & Jove, 1993) and more intriguingly p190rho-GAP has been shown to be a substrate of mammalian low molecular weight PTPase . Furthermore it has been reported that phosphorylation of mammalian GAP by the src tyrosine kinase reduces GAP activity (Giglione, Gonfloni, & Parmeggiani, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine phosphorylation of mammalian GAP has long been known (Ellis, Moran, McCormick, & Pawson, 1990;Molloy et al, 1989;Park & Jove, 1993) and more intriguingly p190rho-GAP has been shown to be a substrate of mammalian low molecular weight PTPase . Furthermore it has been reported that phosphorylation of mammalian GAP by the src tyrosine kinase reduces GAP activity (Giglione, Gonfloni, & Parmeggiani, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that FGFR-1 activation leads to phosphorylation of Shc and activation of Raf-1 and MAPK (Klint et al, 1995;Shaoul et al, 1995;Wang et al, 1994) whereas other signal transduction molecules which have been implicated in chemotactic signaling i.e. PI 3-kinase and rasGAP do not bind to or become activated by FGFR-1 (Molloy et al, 1989;WennstroÈ m et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…p125 GAP is a cytosolic polypeptide that catalyzes the GTPase activity of p21 ras [6,7]. In growth ft~ctor-stimulated and tyrosine kinase-transformed rat fibrobasts, p125 GAP becomes tyrosine phosphorylated and is t~anslocated from the cytosol to cell membranes, where it interacts with its biological target, p21 ras, as well as with actiwlted growth factor receptors [8][9][10][11][12][13][14][15][16][17][18]. It has been reported that p21 ras is responsible for the activation of mitogen-activated protein (MAP) kinases cascade [19], and that MAP kinases are fiwolved in the mechanisms of activation of NADPH oxidase [20][21][22], the enzymatic system responsible for the generation of reactive oxygen metabolites [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%